Why should I be moral? - Hooker, B; Hooker, Bradford Williamson (1986)
﻿ I begin my discussion of the question 'Why should I be moral?' by drawing distinctions both between possible different senses of 'moral' and also between different conceptions of what morality requires. I then criticize the idea that one should be moral because it serves self-interest. Self-interest is served by one's having benevolent concern for only a fairly small number of others, but being moral involves more than this. Furthermore, having moral dispositions other than benevolence is in one's interest only if these dispositions are required by the moral code predominant in one's society. Moreover, even if we confine our attention to people who live in such a society, each person would probably be better off with moral dispositions that were not so strong that they would always get their way, but the completely moral person would presumably have overriding moral dispositions. Finally, having the correct moral beliefs may not be in one's interest. But whatever the gap between self-interest and morality, might one not have most reason to be moral? Derek Parfit has recently argued that the view that one has most reason to do whatever best achieves one's present aims (and these may sometimes be moral aims) is at least as good as the view that one has most reason to do what best promotes one's own long-term good. I attack some of his arguments. But I then go on to argue that moral requirements as such—i.e., independently of whether they are reflected in present desires—do generate reasons for action. But are these moral reasons always stronger than reasons of other kinds? On the basis of an example I describe in the closing pages, I reluctantly conclude that they are not.